PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Mohammad Wisolus Solihin; Sri Handono Budi Prasutowo; Supeno Supeno (FKIP Universitas Jember, 2018)
In this 21st century, through the study of science is expected to guide the students meet 21st century skills. One of the skills that must be mastered is the ability to think critically. It is necessary for effective learning in order to deliver the students to achieve the critical thinking skills. Inquiry model train students to solve problems, make decisions, gain critical thinking skills in analyzing information. In the guided inquiry learning model student plays an active role in doing practical work to solve problems, while teachers could help students if students have problems. The purpose of this study was to determine the effect of guided inquiry learning model on critical thinking skills. Analysis of the data used ins this study is statistic test using test independent sample t-test. Results from this study is the average value of critical thinking skills through post-test 67 in the experimental class and 62.5 in the control class. 1-tailed significance value of statistical test by independent sample T-test of 0.0025, meaning that guided inquiry learning model significantly influence students' critical thinking skills.Key word: Education, Critical Thinking, Guided Inquiry